The Geraniin-Rich Extract from Reunion Island Endemic Medicinal Plant Phyllanthus phillyreifolius Inhibits Zika and Dengue Virus Infection at Non-Toxic Effect Doses in Zebrafish - Juliano G. Haddad; Dovilė Grauzdytė; Andrea Cristine Koishi; Wildriss Viranaicken; Petras Rimantas Venskutonis; Claudia Nunes Duarte dos Santos; Philippe Desprès; Nicolas Diotel; Chaker El Kalamouni (Molecules, 2020)
The mosquito-borne viruses dengue (DENV) and Zika (ZIKV) viruses are two medically important pathogens in tropical and subtropical regions of the world. There is an urgent need of therapeutics against DENV and ZIKV, and medicinal plants are considered as a promising source of antiviral bioactive metabolites. In the present study, we evaluated the ability of Phyllanthus phillyreifolius, an endemic medicinal plant from Reunion Island, to prevent DENV and ZIKV infection in human cells. At non-cytotoxic concentration in vitro, incubation of infected A549 cells with a P. phillyreifolius extract or its major active phytochemical geraniin resulted in a dramatic reduction of virus progeny production for ZIKV as well as four serotypes of DENV. Virological assays showed that P. phillyreifolius extract-mediated virus inhibition relates to a blockade in internalization of virus particles into the host cell. Infectivity studies on ZIKV showed that both P. phillyreifolius and geraniin cause a loss of infectivity of the viral particles. Using a zebrafish model, we demonstrated that administration of P. phillyreifolius and geraniin has no effect on zebrafish locomotor activity while no morbidity nor mortality was observed up to 5 days post-inoculation. Thus, P. phillyreifolius could act as an important source of plant metabolite geraniin which is a promising antiviral compound in the fight against DENV and ZIKV.